Hybrid Perventricular Ventricular Septal Defect Device Closure in a 3-Months Old Infant with Severe Failure to Thrive - Akhtar, Khurrum; Imtiaz, Sana; Rafique, Saima; Kamal, Dawood; Ahmad, Kaleem; Ara, Andaleeb; Sadiq, Nadeem; Rehman, Mujeeb Ur (Pakistan Armed Forces Medical Journal, 2023)
We report a case of successful hybrid device closure of large mid muscular Ventricular Septal Defect (VSD) in an infant for the very first time in Pakistan. Increasing collaboration between pediatric cardiac interventionalists and congenital cardiac surgeons has resulted in introduction of various hybrid procedures in the management of Congenital Heart Diseases (CHD). Advantages of hybrid procedures include complex interventions by using minimally invasive methods, avoidance of cardiopulmonary bypass, shorter procedure and recovery time leading to subsequent decrease in complications. A large VSD in an infant carries an increased risk of morbidity including failure to thrive, congestive cardiac failure, and recurrentrespiratory tract infections. Timely and safely the successful perventricular closure of large VSD using hybrid approach is a milestone in the management of VSDs in infants.